BIM-Based Quantity Take-off for Reinforced Concrete Structure Works in Educational Building Construction Project - Arvan Dani; Risma Apdeni; Zel Citra (CIVED, 2025)
The use of Building Information Modeling (BIM) in Indonesia is still limited and not yet common. One of the benefits of Building Information Modeling (BIM) is to improve efficiency in calculating the amount of work. Quantity Take-off calculations are often done conventionally by measuring shop drawings manually, which can lead to errors due to inaccuracies and complexities in calculating the volume of work. One software that can assist in designing, simulating, and visualizing buildings is Autodesk Revit software. The calculation process is done by converting 2D Detailed Engineering Design (DED) drawings into 3D drawings using Revit 2024 software. The case study of this research is the Construction Project of the Guest House Building at the University of Riau, Pekanbaru City, Riau Province. The research process involves modeling based on references from shop drawings, followed by performing quantity take-off calculations on the building structure work. The output of the modeling shows the results of calculating the volume of concrete needed for the building structure and the quantity of steel reinforcement from the building structure. Based on the calculation results, the volume of concrete needed for the conventional method is 391.197 m3, which when multiplied by AHSP results in a total cost of Rp 762,376,997.19. Meanwhile, the total volume using Autodesk Revit 2024 is 318,213 m3 with a total cost of Rp 620,942.778,00. For the reinforcement work of the structure, the Autodesk Revit calculation results in Rp 1,952.501.845,31, while the results from the conventional method amount to Rp 3,697.279.792,12. It can be concluded that the calculation results using Building Information Modeling (BIM) method are smaller than the calculations using the conventional method.